The Oxford History of World Cinema - Nowell-Smith, Geoffrey (Oxford University Press, 1997)
The Oxford History of World Cinema, written by an international team of distinguished contributors, traces the history of the twentieth century's most enduringly popular entertainment from across the globe. Covering all aspects of its development, stars, studios, and cultural impact, the book celebrates and chronicles one hundred years of diverse achievement from westerns to the New Wave, from animation to the Avant-garde, and from Hollywood to Hong Kong. Illustrated. throughout. - ;From its humble beginnings as a novelty in a handful of cities, cinema has risen to become a billion- dollar ind.